2020
DOI: 10.1039/d0dt01107j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antiparasitic activity of organometallic derivatives of the anthelmintic drug albendazole

Abstract: A series of new ferrocenyl and ruthenocenyl derivatives of the organic drug albendazole have been prepared and their activity against different helminths and protozoans assessed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Albendazole is an oral, broad-spectrum, anthelmintic agent of the benzimidazole class that is commonly used in the treatment of trichinellosis, toxocariasis and other nematode infection in addition to echinococcosis and cysticercosis (Hong, 2018, Verma et al, 2018and Lin et al, 2020. Albendazole is more effective in early stage of trichinellosis than in late stage (Eid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Albendazole is an oral, broad-spectrum, anthelmintic agent of the benzimidazole class that is commonly used in the treatment of trichinellosis, toxocariasis and other nematode infection in addition to echinococcosis and cysticercosis (Hong, 2018, Verma et al, 2018and Lin et al, 2020. Albendazole is more effective in early stage of trichinellosis than in late stage (Eid et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Helminths, also known as flukes, roundworms, and tapeworms, are parasitic worms that look like worms. Other anthelmintics are poorly absorbed via the gut, exposing the parasite to considerably higher anthelmintic concentrations than the host [1][2][3] . The term "anthelmintic" refers to a medicine used to treat parasitic worm infestations in animals.…”
Section: Anthelminticsmentioning
confidence: 99%
“…15,16 In addition, extensive studies by Meggers et al and others have shown that the functionalization of bioactive organic molecules with an inert metal core can improve the affinity and selectivity of enzyme inhibitors. 17–21…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition, extensive studies by Meggers et al and others have shown that the functionalization of bioactive organic molecules with an inert metal core can improve the affinity and selectivity of enzyme inhibitors. [17][18][19][20][21] With respect to SARS-CoV-2, high-throughput screening (HTS) identied the organoselenium compound Ebselen as an inhibitor of SARS-CoV-2 infection in Vero E6 cells with low micromolar activity. 22 Based on these results, other studies have sought to optimize the activity of Ebselen toward SARS-CoV-2, but with limited success.…”
Section: Introductionmentioning
confidence: 99%